Stolen - Christopher, Lucy. (New York : Chicken House, 2012)
British city-dweller Gemma is abducted while on vacation and taken to the Australian outback, where she realizes that escape attempts are futile, and in time she learns that her captor is not as despicable as she first believed.
Reprint. Originally published: 2010.
Includes excerpt from the author's forthcoming book.
Michael L. Printz Award for Excellence in Young Adult Literature
Keywords: Kidnapping -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Adventure stories; Australia -- Juvenile fiction